Preparation, characterization and in vivo evaluation of bergenin-phospholipid complex - Qin Xuan; Yang Yang; Fan Ting-ting; Gong Tao; Zhang Xiao-ning; Huang Yuan (Acta Pharmacologica Sinica, 2016)
Aim: To prepare a bergenin-phospholipid complex (BPC) to increase oral bioavailability of the drug. Methods: In order to obtain the acceptable BPC, a spherical symmetric design-response surface methodology was used for process optimization. The infl uence of reaction medium, temperature, drug concentration and drug-to-phospholipid ratio on the combination percentage and content of bergenin in BPC were evaluated. BPC was then characterized by thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC), ultra-violet (UV) spectroscopy, fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC) and X-ray powder diffraction. The physicochemical properties such as microscopic shape, particle size, zetapotential, solubility, crystalline form, and hygroscopicity were tested. The pharmacokinetic characteristics and bioavailability of BPC were investigated after oral administration in rats in comparison to bergenin and the physical mixture (bergenin and phospholipids). Results: BPC was successfully prepared under the optimum conditions [temperature=60 °C, drug concentration=80 g/L and drug-tophospholipids ratio=0.9 (w/w)]. The combination percentage was 100.00%±0.20%, and the content of bergenin in the complex was 45.98%±1.12%. Scanning electron microscopy and transmission electron microscopy of BPC showed spherical particles. The average particle size was 169.2±20.11 nm and the zeta-potential was −21.6±2.4 mV. The solubility of BPC in water and in n-octanol was effectively enhanced. The Cmax and AUC0→∞ of BPC were increased, and the relative bioavailability was signifi cantly increased to 439% of bergenin. Conclusion: The BPC is a valuable delivery system to enhance the oral absorption of bergenin.